Meningkatkan Prestasi Belajar Akidah Akhlak Melalui Penerapan Model Pembelajaran Mastery Learning bagi Siswa MTs. Hidayaturrahman NW Menggala - Sahari Sahari (Universitas Pendidikan Mandalika, 2020)
The purpose of this study was to improve student learning outcomes through the implementation of teacher strategies using Mastery Learning in learning akidah akhlak at MTs. Hidayaturrahman NW Menggala. The method used in this research is classroom action research which consists of 2 cycles. The subjects of this study were students of class VII-A MTs Hidayaturrahman NW Menggala. The data collection techniques used were observation, interviews and tests. While the data analysis technique used is descriptive qualitative and quantitative. The results of this study indicate that the percentage results of each cycle are: (1) Pre-Cycle, the average value of student learning outcomes is 62.71%; (2) Cycle I, the resulting average value is 71.337%; and (3) Cycle II, the resulting average value is 83.33%. So based on these results it can be concluded that student learning outcomes increase with the application of the mastery learning learning model.